Exploring Self-Regulated Learning and ICT Integration in Chemistry Education: A Study in the Digital Era - Munawwarah Munawwarah; Sumiati Side (Science Education and Application Journal, 2025)
Profiling Self-Regulated Learning and ICT Utilization among Chemistry Education Students in the Digital Era. In the digital era, chemistry education faces dual challenges: fostering students’ self-regulated learning (SRL) while optimizing the use of information and communication technology (ICT). This study aims to profile the levels of SRL and the extent of ICT utilization among chemistry education students, providing insights into how both aspects intersect in supporting academic success. A descriptive quantitative design was employed, involving 26 third-year chemistry education students at Universitas Negeri Makassar. Data were collected through two instruments: an SRL questionnaire covering dimensions of goal setting, planning, time management, learning strategies, self-monitoring, motivation, and self-reflection, and an ICT utilization questionnaire addressing access to digital resources, use of learning applications, participation in online discussions, digital collaboration, and creativity in ICT-supported chemistry learning. Responses were analyzed using descriptive statistics and thematic analysis of open-ended items. The results revealed that students’ SRL abilities ranged from moderate to high, with notable strengths in goal setting, planning, and reflection, but persistent challenges in time management and independent study. In contrast, ICT utilization was consistently high across all dimensions, showing strong reliance on digital resources and collaborative tools. A comparative analysis indicated that students rely more on external ICT support than on internal self-regulatory strategies. The study concludes that while ICT integration in learning is robust, strengthening SRL remains essential to balance technology use with sustainable learning autonomy. These findings suggest the need for instructional designs that deliberately embed SRL-enhancing components into ICT-based learning, aligning with the demands of the digital era and the pursuit of quality education